The Effect of Trained Peer Feedback on Narrative Text among low English Language Proficiency - Achmad Zainudin (Graduate Program, University of Islam Malang, 2019)
AbstractThis study examines trained EFL learners peer feedback on narrative text in the context of students with low English language proficiency. Researcher conducted pretest to each students (n=26). They write a narrative text in which the title has been prepared by researcher then they review their peer writing. After that, students are given two coaching peer feedback. Each meeting is eighty minutes. After that researcher conducted posttest and compare pretest and posttest. Result showed that students who obtained training peer feedback are better than before getting trained peer feedback on their writing ability although it is not significant result. The improvement of students’ score can be seen from the difference both pretest and posttest. The mean score of pretest improved from 56 to 66.31. The researcher concludes that the extensive training will implicate to the significant result of their writing and it enhanced critical thinking of LP students. Keywords: EFL writing, peer feedback, peer feedback training